User Satisfaction Analysis of SMOPI Application: The Role of User Interface, Perceived Ease of Use, and Behavioral Intention at the Irrigation Engineering Center - Ministry of Public Works and Public Housing - Iman, Azharul; Fauzan Azhmy, Muhammad; Indahwati, Rini (Sumber Belajar Sejahtera, 2025)
This research analyzed how the user interface, perceived ease of use, and behavioral intention impact user satisfaction with the SMOPI application based on the technology acceptance model. A quantitative survey using a cross-sectional design collected data from application users through sampling. Structural equation modeling with SMARTPLS analyzed the results. The findings demonstrated that the user interface significantly influenced satisfaction, with a path coefficient of 0.645 and P-value of 0.021, indicating a comfortable and relevant interface enhances satisfaction. However, perceived ease of use and behavioral intention did not significantly impact satisfaction, recording path coefficients of -0.015 (P-value 0.947) and 0.189 (P-value 0.591), respectively. In closing, the user interface emerged as the most consequential factor in determining satisfaction with the SMOPI application. Optimizing features to align with consumer needs while refining the design were recommended to boost satisfaction overall. Adopting the technology acceptance model in this research provided useful insights into user acceptance and the satisfaction-influencing elements.